Asuhan Keperawatan Keluarga Dengan Diabetes Mellitus - Mega Hartati; Lucia Firsty Puspita Khrisna (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2018)
The family is the smallest unit of the community consisting of the head of the family and several people who gather and live in a place under one roof in a state of mutual dependence. The family is used as a service unit because family health problems are interrelated and influence each other among family members and will also affect surrounding families or the community. One problem that can affect family family health is Diabetes Mellitus. Diabetes Mellitus is a health problem that can reduce the productivity of human resources. Diabetes Mellitus is a progressive chronic disease characterized by the inability of the body to metabolize carbohydrates, fats, and proteins, leading to hyperglycemia. One of the causes of Diabetes Mellitus is an unhealthy diet, such as foods that contain lots of high sugar levels that can lead to increased blood sugar levels. Unhealthy lifestyles can also trigger Diabetes Mellitus such as rarely exercising, smoking, and drinking alcoholic beverages. To be able to overcome problems in families with Diabetes Mellitus, namely by providing comprehensive nursing care by using the nursing process in which nurses have an important role in providing nursing care that is on aspects of promotive, preventive, curative, and rehabilitative